Joint Influence of Steered Vacuum Arc and Negative Repetitively Pulsed Bias on Macroparticles Suppression; The 19th International Conference on Surface Modification of Materials by Ion Beams (SMMIB-2015), November 22-27, 2015, The Empress Hotel, Chiang Mai, Thailand - Ryabchikov A. I. Aleksandr Ilyich; Ananin P. S. Petr Semenovich; Shevelev A. E. Aleksey Eduardovich; Sivin D. O. Denis Olegovich; Zhelomsky S. G. Sergey Gennadjevich (2015, 2015)
В фонде НТБ ТПУ отсутствует